Liberalism and the postcolony thinking the state in 20th-century Philippines - Claudio, Lisandro E. (Kyoto-CEAS series on Asian studies, 2017)
The Philippines entered the twentieth century newly free of Spanish rule and faced with the task of building a nation. Due in part to American control of the country for the first half of the twentieth century, liberalism played a dynamic role in shaping the government and philosophy of the Philippines.